A toponímia rural no contexto cafeicultor da Serra do Caparaó - Jacqueline Helen de Lima (2021)
The study of toponymy is of great importance for understanding and knowledge of the historical and socio-cultural aspects of a region. Through it, it is possible to identify linguistic occurrences that reveal the ideologies and beliefs of a people in the denominational act and also verify the permanence or disappearance of a name in a community. In this sense, this research aimed to carry out a descriptive study (linguistic-historic-cultural) of the rural toponymic lexicon of the municipalities of Alto Caparaó, Caparaó and Espera Feliz, major coffee producers in the Serra do Caparaó region, in eastern Minas Gerais. The focus of this study is the name of the physical and human accidents found in rural areas in such cities. The concept of the inseparability between language and culture was adopted, as exposed by Duranti (2000) and Biderman (2001). The theoretical framework was developed by Biderman (2001). The theoretical-methodological assumptions of onomastic science used were developed by Dick (1990a, 1990b). This study is linked to the ATEMIG Project (Toponymic Atlas of the State of Minas Gerais), started in 2005 at the Faculty of Letters of the Federal University of Minas Gerais and to the Minas Gerais Group of Lexicon Studies (GruMEL/UFMG/CNPq). For the construction of the toponymic corpus, data were collected from the reading and analysis of the geographic maps of the year 2010, from the three municipalities, provided by IBGE (Brazilian Institute of Geography and Research), with a scale of 1: 50,000. Thus, 199 toponyms were found, which were organized in toponymic forms. The information explained in the forms are: the place name, the taxonomy, the nature of the place name, the accident and the nature of the accident. A quantitative study of toponyms and accidents was carried out, which was the basis for the toponymic analysis. This research showed that, in addition to the linguistic study, the investigation of place names also provides an analysis of the relationship between man and the environment in which he lives, recovering cultural, ideological and historical information concerning the occupation and organization of this region of the state of Minas Gerais.